PENGARUH VARIASI CAMPURAN BIODIESEL MINYAK JELANTAH TERHADAP KARAKTERISTIK PEMBAKARAN PADA MESIN DIESEL - Berthy Pelasula; R.R Lekatompessy; NJM Nanulaitta; Graciadiana I Huka; Hendry de Fretes (Journal Mechanical Engineering, 2025)
This study investigates the transient behavior of internal combustion engines (SI Engine) using various ethanol-gasoline blends (E0 to E10). The research aims to analyze the impact of bioethanol concentration on engine stability across two operational regimes: low speed (1500 RPM) simulating idle conditions and medium speed (2000 RPM) representing transition to workload. The experimental method involved sequential microscopic recording of crankshaft fluctuations at specific intervals. The results demonstrate that at 1500 RPM, E10 significantly improves operational stability, reducing fluctuations to only 10 RPM compared to 60 RPM for E0, due to the oxygenated nature of ethanol. Conversely, at 2000 RPM, higher ethanol concentrations (E8 and E10) lead to performance deficits and unstable combustion phases. This is attributed to the lower heating value (LHV) of ethanol, which results in a 3% to 4% reduction in chemical energy input, and high latent heat of vaporization that causes intake cooling and non-uniform vaporization.  Key word : bioethanol, SI engine, engine stability, fluctuations RPM